The Effects of Selective Harvest on Japanese Spanish Mackerel (Scomberomorus niphonius) Phenotypic Evolution - Sun, Peng; Shang, Yangke; Sun, Runlong; Tian, Yongjun; Heino, Mikko (Frontiers in Ecology and Evolution, 2022)
Japanese Spanish mackerel (Scomberomorus niphonius) is an important fish species in the China Seas with wide distribution, extensive migration, and high economic value. This species has been yielding high fisheries production despite experiencing continuously high fishing pressure and the conversion from gillnet to trawl harvesting. Meanwhile, changes in life-history traits have been observed, including earlier maturation and smaller size at age. Here, we build an individual-based eco-genetic model parameterized for Japanese Spanish mackerel to investigate the population’s response to different fishing scenarios (fishing by trawl or by gillnet). The model allows evolution of life-history processes including maturation, reproduction and growth. It also incorporates environmental variability, phenotypic plasticity, and density-dependent feedbacks. Our results show that different gear types can result in different responses of life-history traits and altered population dynamics. The population harvested by gillnet shows weaker response to fishing than that by trawl. When fishing ceases, gillnet-harvested population can recover to the pre-harvest level more easily than that harvested by trawl. The different responses of population growth rate and evolution to different fishing gears demonstrated in this study shed light on the sustainable management and utilization of Japanese Spanish mackerel in the over-exploited China Seas.